A Study to Determine the Link between Media Use and Drug Use among Students: A Case Study of Pakistan - Mujeeb-ur-Rehman Abro; Akhlaque Hussain Larik; Muhammad Ramzan; Sahib Oad (Progressive Research Journal of Arts & Humanities (PRJAH), 2024)
In Pakistan, drug addiction is becoming more common as the country has 6.7 million drug users. A serious social issue facing modern Pakistani society is a rapid rise in drug addiction among students. Drug traffickers have stepped up the use of media to trigger demand for drugs in many countries including Pakistan, India, and Thailand. The media had a significant impact on their decision to start abusing drugs. Previous studies show media encourages teen substance use. So, this study is designed to determine the link between the use of media and drug use among students in two universities in Khairpur City. An exploratory research method was employed because society is traditional and no substantive research has been carried out on the issue in the country. A random sampling technique was adopted to collect data. The target population for this study was students of two Universities in Khairpur. An online close-ended questionnaire was adopted and distributed among students of two universities online. Python was employed to analyze the data. Results establish links between the use of media and drug use among the students. Moreover, students spending two hours on social media are exposed to information related to drugs, which puts them at increased risk of drug use.